2022
DOI: 10.1142/s1363919622500402
|View full text |Cite
|
Sign up to set email alerts
|

Do Dynamic Capabilities Facilitate Business Model Innovation in Small and Medium-Sized Chinese Family Companies?

Abstract: This study investigates whether small- and medium-sized enterprises (SMEs) under family influence (FI) can achieve business model innovation (BMI) through dynamic capabilities (DCs) as promoted by prior research. Overall, 259 small and medium-sized family firms in Southeastern China were examined and analysed using the partial least squares structural equation modelling (PLS-SEM) method. The findings showed a direct negative link between FI-DCs (sensing, seizing, and transforming capabilities), sensing capabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 120 publications
0
4
0
Order By: Relevance
“…Bitetti and Gibbert (2022) identify four sensing capabilities – responding, overturning, anticipating, dribbling (ROAD) – involved in initiating BMI processes. Further researchers have analyzed BMI through DC in small- and medium-sized family enterprises; findings of empirical studies in this area show a positive link between seizing capabilities and value creation (Huang and Ichikohji, 2022). Furthermore, research has identified drivers for BMI and spotlighted the role of DC.…”
Section: Resultsmentioning
confidence: 99%
“…Bitetti and Gibbert (2022) identify four sensing capabilities – responding, overturning, anticipating, dribbling (ROAD) – involved in initiating BMI processes. Further researchers have analyzed BMI through DC in small- and medium-sized family enterprises; findings of empirical studies in this area show a positive link between seizing capabilities and value creation (Huang and Ichikohji, 2022). Furthermore, research has identified drivers for BMI and spotlighted the role of DC.…”
Section: Resultsmentioning
confidence: 99%
“…The concept of dynamic capabilities is important within strategic management because the resource-based perspective was unable to explain how and why certain organizations achieve sustainable competitive advantages in situations of rapid and unpredictable changes (Nedzinskas et al, 2013). Under the RBV perspective, companies are seen as a set of tangible and intangible resources and researchers affirm that the only way to obtain competitive advantage is through the acquisition and possession of valuable, rare, inimitable, and non-replaceable resources (Huang & Ichikohji, 2022;Nedzinskas et al, 2013). However, Teece et al (1997) pointed out that there is an alternative way to generate competitive advantages, called dynamic capabilities, a concept that emphasizes two key aspects that were not covered by the RBV: (a) dynamic, which highlights the ability of an organization to renew its competencies and achieve congruence with the changing environment; and, (b) capabilities, which refers to the key role of strategic management to adapt, integrate, and appropriately reconfigure internal and external organizational skills, resources, and functional competencies and thus be able to adapt to the constantly changing environment requirements (Teece, 2018).…”
Section: Dynamic Capabilitiesmentioning
confidence: 99%
“…Similarly, Huang and Ichikohji (2022) conducted a study on 259 Chinese manufacturing SMEs and found that GDC positively influences the adoption of GI, which in turn leads to improved environmental performance. To achieve GI, an organization must utilize and reconfigure internal and external dynamic capacities (Lin & Chen, 2016).…”
Section: Gdc and Gimentioning
confidence: 99%